Causes of Death and Cardiovascular Comorbidities in Adults With Congenital Heart Disease. Issue 14 (21st July 2020) - Goldstein, Sarah A.; D'Ottavio, Alfred; Spears, Tracy; Chiswell, Karen; Hartman, Robert J.; Krasuski, Richard A.; Kemper, Alex R.; Meyer, Robert E.; Hoffman, Timothy M.; Walsh, Michael J.; Sang, Charlie J.; Paolillo, Joseph; et al.
Abstract : Background: Little is known about the contemporary mortality experience among adults with congenital heart disease (CHD). The objectives of this study were to assess the age at death, presence of cardiovascular comorbidities, and most common causes of death among adults with CHD in a contemporary cohort within the United States. Methods and Results: Patients with CHD who had a healthcare encounter between 2008 and 2013 at 1 of 5 comprehensive CHD centers in North Carolina were identified by International Classification of Diseases, Ninth Revision ( ICD‐9 ), code. Only patients who could be linked to a North Carolina death certificate between 2008 and 2016 and with age at death ≥20 years were included. Median age at death and underlying cause of death based on death certificate data were analyzed. The prevalence of acquired cardiovascular risk factors was determined from electronic medical record data. Among the 629 included patients, the median age at death was 64.2 years. Those with severe CHD (n=157, 25%), shunts (n=202, 32%), and valvular lesions (n=174, 28%) had a median age at death of 46.0, 65.0, and 73.3 years, respectively. Cardiovascular death was most common in adults with severe CHD (60%), with 40% of those deaths caused by CHD. Malignancy and ischemic heart disease were the most common causes of death in adults with nonsevere CHD. Hypertension and hyperlipidemia were common comorbidities among all CHD severity groups. Conclusions: The most common underlying causes of death differed by lesion severity. Those with severe lesions most commonly died from underlying CHD, whereas those with nonsevere disease more commonly died from non‐CHD causes.